Near‐seabed sediment dynamics and fluxes on Chatham Rise, the effects of seabed disturbance, and implications for deep‐sea bottom trawling and seabed mining - Scott D. Nodder; Christopher A. Eager; Joe O’Callaghan; Daniel Leduc; Sam Davidson; Stacy Deppeler; Grace Frontin‐Rollet; Peter Gerring; Sarah Searson; William Quinn; Steve George; Ron Ovenden; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
Anthropogenic impacts are increasingly affecting deep‐sea environments, including seafloor sediment disturbances by bottom trawling and seafloor mining. Fieldwork in the ‘Resilience Of Benthic Ecosystems to Sedimentation’ (ROBES) project were conducted in 2018–2020 on the 400 m‐deep Chatham Rise crest, eastern Aotearoa New Zealand. Water column turbidity data, sediment traps on near‐seabed moorings and benthic landers and surficial sediments from multi‐corers provided baseline and post‐impact information following an artificially induced seafloor disturbance event in June 2019 using a modified harrow plough in and around an elongated bathymetric depression, designated as the ‘Butterknife’. During the disturbance, total mass and particulate organic carbon (POC) near‐bed fluxes were elevated above long‐term fluxes (2018–20). Long‐term 2018–19 fluxes were generally less than in 2019–20, driven by interannual oceanographic variations. These results, coupled with 50–100 m‐thick benthic boundary layers, suggest that lateral advection is a dominant process in the resuspension and redistribution of seafloor sediments on the rise. Further research is required to better understand the longer term dynamics of particle transport and deposition in response to human activities, such as bottom trawling or proposed phosphorite seafloor mining, especially in bathyal environments, such as the Chatham Rise.

Effects of fine-scale changes in resource access and social stability on the sociality of foraging flocks of wild birds - Camille A. Troisi; Josh A. Firth; Sam J. Crofts; Gabrielle L. Davidson; Michael S. Reichert; John L. Quinn (Animal Behaviour, 2025)

A review of approaches for submarine landslide-tsunami hazard identification and assessment - Jean H.M. Roger; Suzanne Bull; Sally J. Watson; Christof Mueller; Jess I.T. Hillman; Andrea Wolter; Geoffroy Lamarche; William Power; Emily Lane; Susi Woelz; Sam Davidson (Marine and Petroleum Geology, 2024)

Diversity and host specificity of the Verminephrobacter –earthworm symbiosis - Marie B. Lund; Seana K. Davidson; Martin Holmstrup; Sam James; Kasper U. Kjeldsen; David A. Stahl; Andreas Schramm (Environmental Microbiology, 2010)
Summary Symbiotic bacteria of the genus Verminephrobacter ( Betaproteobacteria ) were detected in the nephridia of 19 out of 23 investigated earthworm species ( Oligochaeta : Lumbricidae ) by 16S rRNA gene sequence analysis and fluorescence in situ hybridization (FISH). While all four Lumbricus species and three out of five Aporrectodea species were densely colonized by a mono‐species culture of Verminephrobacter , other earthworm species contained mixed bacterial populations with varying proportions of Verminephrobacter ; four species did not contain Verminephrobacter at all. The Verminephrobacter symbionts could be grouped into earthworm species‐specific sequence clusters based on their 16S rRNA and RNA polymerase subunit B ( rpoB ) genes. Closely related host species harboured more closely related symbionts than did distantly related hosts. Co‐diversification of the symbiotic partners could not be demonstrated unambiguously due to the poor resolution of the host phylogeny [based on histone H3 and cytochrome c oxidase subunit I (COI) gene sequence analyses]. However, there was a pattern of symbiont diversification within four groups of closely related hosts. The mean rate of symbiont 16S rRNA gene evolution was determined using a relaxed clock model, and the rate was calibrated with paleogeographical estimates of the time of origin of Lumbricid earthworms. The calibrated rates of symbiont 16S rRNA gene evolution are 0.012–0.026 substitutions per site per 50 million years and thus similar to rates reported from other symbiotic bacteria.